If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -6 = -2(-6x + 3) Reorder the terms: -6 + 12x = -2(-6x + 3) Reorder the terms: -6 + 12x = -2(3 + -6x) -6 + 12x = (3 * -2 + -6x * -2) -6 + 12x = (-6 + 12x) Add '6' to each side of the equation. -6 + 6 + 12x = -6 + 6 + 12x Combine like terms: -6 + 6 = 0 0 + 12x = -6 + 6 + 12x 12x = -6 + 6 + 12x Combine like terms: -6 + 6 = 0 12x = 0 + 12x 12x = 12x Add '-12x' to each side of the equation. 12x + -12x = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 13x+3y=-17 | | -8x+14x= | | -34+24= | | (x-8)=(23+x) | | 2/3c+6=-2 | | (3/5)x=(-4/7)+x | | 4v+19=-5v-17 | | 7x+4/5=5x-2/6 | | 2b-2/2b^2-8=0 | | 10=40 | | 120=x+2x/3 | | 7(a-2)-6=2(a+4)+a | | -4/3v+5/3v=1/5-2/5 | | (4x+10)=110 | | 16=8(4/x) | | 6a-8-3ab+4ab=0 | | -5(3w+3)=-15w+11 | | (3x+20)=(2x+7) | | 5x+16=14x+83 | | 1.5+7.4=1.8x-6.9 | | 1/4y=-9 | | -3+11=13x-2-12x | | z-7/3=8/3 | | -5u=-5/6 | | 2x=8-1/2x | | 1.6n=1.1n | | 10-p+2=-7 | | 24p^9+20p^3/4p | | 5/3=x-1/3 | | 8z-7z=23+21 | | 1+2/9v=4 | | f(x) = 9 x |